An inventory of crop wild relatives of the United States - Khoury, Colin K.; Greene S; Wiersema, John H.; Maxted, Nigel; Jarvis, Andy; Struik, Paul C. (Wiley, 2013)
The use of crop wild relatives (CWRs) in breeding is likely to continue to intensify as utilization techniques improve and crop adaptation to climate change becomes more pressing. Significant gaps remain in the conservation of these genetic resources. As a first step toward a national strategy for the conservation of CWRs, we present an inventory of taxa occurring in the United States, with suggested prioritization of species based on potential value in crop improvement. We listed 4600 taxa from 985 genera and 194 plant families, including CWRs of potential value via breeding as well as wild species of direct use for food, forage, medicine, herb, ornamental, and/or environmental restoration purposes. United States CWRs are related to a broad range of important food, forage and feed, medicinal, ornamental, and industrial crops. Some potentially valuable species are threatened in the wild, including relatives of sunflower (Helianthus annuus L.), walnut (Juglans regia L.), pepo squash (Cucurbita pepo L.), wild rice (Zizania L.), raspberry (Rubus idaeus L.), and plum (Prunus salicina Lindl.), and few accessions of such taxa are currently conserved ex situ. We prioritize 821 taxa from 69 genera primarily related to major food crops, particularly the approximately 285 native taxa from 30 genera that are most closely related to such crops. Both the urgent collection for ex situ conservation and the management of such taxa in protected areas are warranted, necessitating partnerships between concerned organizations, aligned with regional and global initiatives to conserve and provide access to CWR diversity.